A cross-sectional study on drug use in multiple system atrophy - Rey, María Verónica (2014)
BACKGROUND: Drug use has rarely been studied in multiple system atrophy (MSA) while such patients receive many treatments based on weak evidence. OBJECTIVE: To analyze drug use from the database of the French MSA Reference Center, and to compare it with data from patients with Parkinson disease (PD). METHODS: Medication of 147 MSA and 180 age- and sex-matched PD patients was analyzed. Motor and autonomic symptoms were explored in MSA patients by the SCOPA-Autonomic and Unified MSA Rating Scale (UMSARS). RESULTS: MSA and PD patients received a mean of five different drugs. MSA patients were more frequently exposed to laxatives, antidiabetic medications, antihypotensives, muscarinic antagonists, alpha-adrenergic blockers, and antidepressants. Levodopa consumption was less in MSA-C (cerebellar) patients compared with MSA-P (parkinsonian) and PD patients. Dopamine agonists were more consumed by PD than MSA patients. MSA patients with more severe disability received more laxatives, anticoagulants, and antidepressants. MSA-P patients received more analgesics. “Probable” MSA patients received more antihypotensives and less alpha-adrenergic blockers. Patients with higher SCOPA-Autonomic scores were more frequently on antihypotensives or antidepressants. Drug associations leading to potential adverse interactions were uncommon (usually <5 %). CONCLUSIONS: Some differences in drug use between MSA and PD patients were observed and expected, including those used for the relief of parkinsonian motor symptoms, autonomic dysfunction, and depression. Many of these drugs are frequently used in MSA in the absence of well-established, positive, benefit-risk evaluations, thus calling for better assessments. The reason why other medications, including anti-diabetic medications, were more consumed by MSA patients remains unclear and deserves further exploration.